2017
DOI: 10.3233/wor-172640
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a novel workstation device on promoting non-exercise activity thermogenesis (NEAT)

Abstract: Modest movement while seated, i.e., use of HOVR, elevated metabolic rate by 17.6% compared to sitting and by 7% compared to standing and might be a reasonable strategy to help elevate NEAT during the workday.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The DJ, on the other hand, involved dynamic contractions of both legs, mimicking a true walking movement. This may explain the higher relative increase in METs (77%-92%) using DJ while Horswill et al (2017) reported an increase of ~1 7% using the HOVR device. The differences in increase in METs between DJ and HOVR may be attributed to the lack of muscle contraction and lack of resistance adjustment in HOVRs.…”
Section: Figurementioning
confidence: 95%
See 2 more Smart Citations
“…The DJ, on the other hand, involved dynamic contractions of both legs, mimicking a true walking movement. This may explain the higher relative increase in METs (77%-92%) using DJ while Horswill et al (2017) reported an increase of ~1 7% using the HOVR device. The differences in increase in METs between DJ and HOVR may be attributed to the lack of muscle contraction and lack of resistance adjustment in HOVRs.…”
Section: Figurementioning
confidence: 95%
“…This research received ethical approval from the Institutional Review Board (IRB). Based on the research reported by Horswill et al (2017) that a sample size of 16 produced significant results, and this study used a repeated measure design with each participant had his/her own baseline measures, a convenient sample of 18 participants (8 males and 10 females) were recruited from university staff and students. Pregnant or nursing women and individuals with joint/hip problems, diabetes, cardiovascular disease and hypertension were excluded.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This, inevitably, has led to a workload reduction and a consequent lower EE ( 43 ). Recently, different published researches suggest solutions to reverse increasing sitting time and encourage daily movement in the working scenario to reduce the risks connected to a sedentary lifestyle ( 20 , 44 , 45 ). New alternative workstations have been thought to increase total physical activity in sedentary workers and improve body composition (i.e., decreasing body fat) ( 46 ).…”
Section: Strategies To Increase Neat At Workmentioning
confidence: 99%
“…The additional EE favored by alternative workstations should increase the NEAT and should be bearable for prolonged periods. However, dynamic workstations may carry limitations due to mental distraction that could affect work productivity or safety ( 45 ). For this reason, the design and engineering of alternative workstations should guarantee the normal execution of working tasks, indeed, workers risk finding themselves sitting on the fence between their NEAT increase and their working yield.…”
Section: Strategies To Increase Neat At Workmentioning
confidence: 99%